Midazolam nasal spray to treat intermittent, stereotypic episodes of frequent seizure activity: pharmacology and clinical role, a comprehensive review - Elyse M. Cornett; Meskerem A. Nemomsa; Bailey Turbeville; Matthew A. Busby; Jessica S. Kaye; Aaron J. Kaye; JooHee Choi; Giovanni F. Ramírez; Giustino Varrassi; Adam M. Kaye; Alan D. Kaye; James Wilson; et al. (Health Psychology Research)
An intranasal formulation of midazolam, Nayzilam, has been FDA-approved to treat intermittent, stereotypic episodes of frequent seizure activity. Nayzilam is easy to administer and can quickly treat seizures that occur outside of the hospital. The intra-nasal route of administration allows non-medical personal to administer the drug which makes it more accessible and user-friendly in the event of a seizure. Many studies have indicated quick cessation of seizures with Nayzilam compared to rectal diazepam, which has been the standard of care treatment. Nayzilam has been proven to be safe and effective for acute seizures in children, deeming it a revolutionary alternative in times where intravenous administration is not possible.